SIZE OF GOVERNMENT AND INDIVIDUAL WELFARE IN COUNTRIES OF THE PACIFIC ALLIANCE - Rodríguez Cairo, Vladimir (2017)
The research allowed to determine the degree of relationship between government size and individual welfare in the Pacific Alliance countries during the period 1970-2014. From this objective, a descriptive analysis was performed on the relationship between the variables and two estimates were used based on the regression analysis and the determination of the correlation coefficient. Thus, the main results obtained show a very positive relationship between the size of the government and the per capita gross domestic product in the Chilean case, and lower in the case of Peru, Mexico and Colombia. Therefore, it was concluded that government size is one of the factors that influenced individual well-being, and consequently, the general well-being of the population, but it is a necessary but not sufficient condition for determining welfare.